COEVOLUTIONARY APPROACHES TO THE ORGANIZATIONAL DEVELOPMENT OF INNOVATION-ACTIVE ENTERPRISES (Development Service Industry Management, 2025)
The article is devoted to a deeper understanding of the organizational boundaries of innovation-active enterprises in the domestic economy, which operates under wartime conditions, based on the demarcation of their structure as organizational and technological systems. The logic behind decision-making in this study is grounded in the efficiency of exchange and the execution of transactions, while the essence of the enterprise is defined by the alignment of incentives, property rights, and rigorous control mechanisms. This approach reveals a more diverse perspective on the boundaries of the enterprise and its technological systems, as well as its theoretical logic and internal organization. Within the framework of an alternative approach, four directions are proposed for discussion:the space of potential efficiency, the domain of organizational influence, the competence-based advantages of innovative production, the identification of the enterprise within an innovation environment. From a legal perspective, the boundaries of an innovation-active enterprise are determined by the following constraints: the effective location of transactions, the conceptualization of influence on other enterprises, the consideration of the enterprise's resource portfolio, the employees' awareness of emotional and cognitive alignment in relation to the innovation process. The "space of potential efficiency" focuses on decisions regarding boundaries as choices about the most effective location for transaction management within the enterprise. The "domain of influence" shifts the notion of organizational boundaries from that of transactional limits to broader boundaries of control. The "competence-based advantages" center on the selection of innovative resources within the enterprise’s portfolio, defining dynamic capabilities for adjusting horizontal and vertical boundaries. "Enterprise identification" within the innovation process takes precedence over efficiency considerations, potentially ignoring empirical evidence of improved management efficiency. However, identification and efficiency may co-evolve as boundaries are mutually shaped during market entry or expansion.
Keywords: innovation; efficiency; organisation; value; power; competence; boundary; control